Monocytes and cancer: promising role as a diagnostic marker and application in therapy - M. R. Patysheva; M. N. Stakheeva; I. V. Larionova; N. A. Tarabanovskaya; E. S. Grigorieva; E. M. Slonimskaya; J. G. Kzhyshkowska; N. V. Cherdyntseva (Бюллетень сибирской медицины, 2019)
Interrelationship between a malignant tumor and the immunity are provided by the involvement of both adaptive and innate immune systems. Monocytes are major participants in nonspecific immune response and mediate their key function through refilling the pool of tumor-associated macrophages, dendritic cells and myeloid suppressor cells. All these populations regulate the relationship of tumor-infiltrating immunocompetent cells with tumor cells and with other components of the microenvironment, as well as tumor cell proliferation, angiogenesis, and dissemination. Monocytes, being direct participants of the chronic persistent inflammation, are involved in the inflammation impact on both tumor origin and progression. The study of the molecular mechanisms of monocyte recruitment and differentiation in malignant neoplasms seems to be a promising direction, both for a diagnostic purpose and as a search for targeting molecules for the control of macrophages and dendritic cells in the tumor microenvironment. In this review, the characteristics of peripheral blood monocytes are given, taking into account the heterogeneity of their population. Tie2+ cells and macrophage-polarized CD163+ and CD204+ -monocytes, as well as cancer-associated macrophage-like cells (CAMLs), are described as contributors to cancer disease progression and outcome. The involvement of monocyte subpopulations in the pathogenesis of oncological diseases of different localizations at the stages of the formation of monocyte precursors in the bone marrow, circulation in peripheral blood and differentiation in tumor tissue is shown.